Pendampingan Pengembangan Produk Pada Kelompok Usaha Bersama Griya Cendekia Playen Gunung Kidul - Muhammad, Hasman Zhafiri; Al Munawwar, Muhammad Luthfi (Universitas Cokroaminoto Yogyakarta, 2025)
Griya Cendekia Playen Yayasan Badan Waqf Universitas Islam Indonesia is located in Padukuhan Tumpak, Kalurahan Ngawu, Kapanewon Playen, Gunungkidul Regency, has various kinds of social community activities including religious guidance, health and productive economic development. Of the various existing activities, productive economic activities have not been able to run well, so they require further assistance, this is the background and focus of this community service program. The purpose of implementing this community service is to be able to utilize existing land, and create MSME products from KUB member mothers. In this community service, the stages of the Community Service Method that will be carried out are 1) Initial coordination with the Griya Cendekia Playen Management, 2) FGD with the Management and members of KUB Griya Cendekia Playen, 3) Utilization of land for waqf land for productive agriculture, 4) Assistance in developing UMKM products, 5) Evaluation and follow-up. The targeted output in this community service is in the form of publication of national journal articles in accordance with the required outputs.